Antisocial features are not predictive of symptom exaggeration in forensic patients - Impelen, Alfons van (Legal and criminological psychology, 2018)
Purpose. To investigate the predictive value of antisocial personality disorder (ASPD) and features of ASPD (i.e., lack of remorse, blame externalization, and deceitfulness) for symptom exaggeration. Methods. A sample of forensic psychiatric patients (N = 57) was asked to complete several self-report instruments (measuring symptom exaggeration, lack of remorse, blame externalization, and offense minimization) and a semi-structured interview about their most recent offense. To quantify patients’ deceitfulness, the information collected via the semi-structured interview was checked against the official records of patient's offenses. Additionally, patient's mental disorders and the extent to which patients denied their delinquency were determined by gathering clinician's judgement on this matter from patient records. The relation between symptom exaggeration and the potential predictors of symptom exaggeration was examined through correlational analyses and cross-tabulation of prevalence rates of symptom exaggeration with prevalence rates of the potential predictors. Results. Antisocial personality disorder was not a useful predicator of symptom exaggeration. Also, patients who showed little regret for their offenses, or tended to blame their offenses on external factors, or minimized their delinquency, or were inaccurate when reporting their delinquency, had similar levels of symptom exaggeration as those without these tendencies. Conclusions. Neither ASPD nor antisocial traits, including lack of remorse, blame externalization, and deceitfulness, were meaningfully related to symptom exaggeration and therefore should have no place in the assessment of symptom validity or the detection of malingering. On the contrary; focusing on antisocial traits as indicators of symptom exaggeration is likely to result in large portions of misclassifications.